2017
DOI: 10.1177/2192568217694141
|View full text |Cite
|
Sign up to set email alerts
|

The Pedicles Are Not the Densest Regions of the Lumbar Vertebrae: Implications for Bone Quality Assessment and Surgical Treatment Strategy

Abstract: Study Design:Cadaver study.Objective:To determine the bone density of lumbar vertebral anatomic subregions. Bone mineral density (BMD) is a major factor in osseous fixation construct strength. The standard region for implant fixation of the spine is the pedicle; however, other regions may be more viable options with higher bone quality.Methods:Using computed tomography images, the spine was digitally isolated by applying a filter for adult bone. The spine model was separated into 5 lumbar vertebrae, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…The reason may be that DEXA, a two-dimensional technique, is unable to capture the threedimensional structure and true volumetric BMD (g/cm 3 ). Hohn et al 29 reported that the effectiveness of the standard procedure for determining spine BMD through DEXA scans may be limited in surgical planning due to its inability to assess the variation of BMD within the vertebrae. In addition, Wang et al 30 demonstrated that the vertebral body contributes on average two-thirds of the vertebral volume in the lumbar spine and only one-third of the BMD.…”
Section: Bmd and Micro-ct Scanningmentioning
confidence: 99%
“…The reason may be that DEXA, a two-dimensional technique, is unable to capture the threedimensional structure and true volumetric BMD (g/cm 3 ). Hohn et al 29 reported that the effectiveness of the standard procedure for determining spine BMD through DEXA scans may be limited in surgical planning due to its inability to assess the variation of BMD within the vertebrae. In addition, Wang et al 30 demonstrated that the vertebral body contributes on average two-thirds of the vertebral volume in the lumbar spine and only one-third of the BMD.…”
Section: Bmd and Micro-ct Scanningmentioning
confidence: 99%
“…A previous study using this method of segmentation produced an average difference in BMD of 1.5% between the first and second measurements of the same anatomical region (SD ±0.7%). 14 The largest percent discrepancy between the repeated measures was 3.0%.…”
Section: Methodsmentioning
confidence: 92%
“…While Hohn et al 14 found the posterior elements to exhibit high total BMD, they do not report other indicators of bone quality such as cortical volume, cortical thickness, and cortical-cancellous bone ratios. BMD may only explain 60% to 70% of the variability in bone strength, while the remaining bone strength is determined by other factors such as the bone geometry, cortical thickness and porosity, and trabecular bone morphology.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations